The genome sequence of the Cranberry Fritillary, Boloria aquilonaris (Stichel, 1908) (Lepidoptera: Nymphalidae) [version 1; peer review: 2 approved] - Charlotte J. Wright; Joana I. Meier; Kay Lucek; Alena Suchackova Bartonova; Hans-Peter Wymann; Mark L. Blaxter (Wellcome Open Research)
We present a genome assembly from a female specimen of Boloria aquilonaris (Cranberry Fritillary; Arthropoda; Insecta; Lepidoptera; Nymphalidae). The assembly contains two haplotypes with total lengths of 415.84 megabases and 390.14 megabases. Most of haplotype 1 (99.86%) is scaffolded into 31 chromosomal pseudomolecules, including the W and Z sex chromosomes. Haplotype 2 was assembled to scaffold level. The mitochondrial genome has also been assembled, with a length of 15.17 kilobases.